Šaurės žemaičių Sedos šnektos balsių psichoakustinė klasifikacija - Mažiulienė, Irena (Kalbotyra, 1995)
The hierarchical classification of the vowels of this Žemitian dialect clearly shows the existence of two principal contrasting auditory classes: the vowels of the older generation - front (i, i., e, ẹ., ie, e, e.) and non-front (back) (a, a., ọ, ọ., uo, u, u.) and the vowels of the younger generation - labial (ọ, ọ., uo, u, u.) and non-labial (i., i., ẹ, ẹ., ie, e, e.).All auditors easily perceive the auditory closeness of ie, uo to the long vowels.The principal auditory classes of the vowels of the older generation coincide with the phonological ones, whereas the younger generation treats them as non-labial, similar to the front vowels. Its “perception of the vowels” is closer to the Aukštaitian pattern of the phonological system.The older generation of Seda perceives the back vowels to be a “a more unified” auditory class, whereas the speakers of the younger generation perceive the front (non-labial) vowels to be “a more unified” auditory class.